The Development of Dragonfly Species Diversity Booklet in Tinjomoyo Tourism Forest as a Supplement Material on Biodiversity Topic - Purnomo, Andri Widi; Rahayuningsih, Margareta (Journal of Biology Education, 2020)
Tinjomoyo Tourism Forest Area is located in Sukorejo, Gunungpati sub-district, Semarang has ​​57.5 hectares with natural potentials, one of them is dragonflies. Dragonflies have an important role because they are a bioindicator for monitoring water quality. The objectives of the study are to analyze dragonflies diversity and describe the feasibility of dragonflies species diversity booklet in Tinjomoyo Tourism Forest used as a supplement of biodiversity material. This study was designed by a modified Research and Development (R&D) research method. The results of observing dragonflies diversity are in three observation lanes in the Tinjomoyo Tourism Forest Area found 27 species, from 7 families of 2 sub-orders with 2 types of which are endemic to the Java island. The overall of index value on the Shannon-Wiener species diversity index scored 2.68, the Evenness index obtained 0.81 and the species dominance index obtained a value of 0.09. The Dragonfly Diversity Booklet that has been developed get very decent criteria to use as supplement material of biodiversity topic for tenth science grade students. The results of the acquisition of 81.82% of material experts and 95.83% of media experts. Teacher responses get a percentage score of 94.44%, responses of students get a percentage of 92% and readability test get a percentage of 92%.